Inferring on Speleomantes Foraging Behavior from Gut Contents Examination - Fabio Cianferoni; Enrico Lunghi (Animals, 2023)
We here provide the first comprehensive analysis and discussion on prey consumed by the European cave salamanders of the genus Speleomantes. Our study stems from the need to shed light on the still unknown foraging behavior adopted by Speleomantes cave salamanders. Starting from the published datasets on gut contents from all Speleomantes species (including hybrids), we here discuss additional information (i.e., species ecology, lower taxonomic level), which were systematically omitted from those data sets. We analyzed a data set consisting of 17,630 records from 49 categories of consumed prey recognized from gut contents of 2060 adults and juveniles Speleomantes. Flying prey accounted for more than 58% of the prey items, while elongated crawling prey accounted for no more than 16% of the diet within a single population. Among the total recognized prey items, only three can be surely ascribed to the group of strictly-cave species (i.e., troglobites), meaning that European cave salamanders mostly forage in surface environment, and therefore represent one of the major drivers of allochthonous organic matter in subterranean environments. Some of the consumed prey seemed to be aquatic, allowing us to hypothesize whether Speleomantes are able to catch prey from a shallow body water. Furthermore, European cave salamanders possess the ability to prey upon taxa characterized by particular anti-predator defenses, while morphological constraints seem to be the most important limit to prey consumption. For each specific case, we provide insights and propose hypotheses concerning the foraging behavior that need to be tested to properly understand the foraging behavior of this cryptic salamanders.